2021
DOI: 10.1002/14651858.cd013121.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Primary prevention of variceal bleeding in people with oesophageal varices due to liver cirrhosis: a network meta-analysis

Abstract: Primary prevention of variceal bleeding in people with oesophageal varices due to liver cirrhosis: a network meta-analysis (Review)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 283 publications
0
8
0
Order By: Relevance
“…Based on low-certainty evidence, a Cochrane meta-analysis showed that beta-blockers, VBL, sclerotherapy and beta-blockers plus nitrates may decrease mortality compared with no intervention in cirrhotic patients with highrisk oesophageal varices without previous bleeding. 689 According to a systematic review with network metaanalysis, monotherapy with nonselective beta-blockers (NSBBs) may decrease all-cause mortality and the risk of first variceal bleeding in patients with cirrhosis with large oesophageal varices and carries a lower risk of serious complications compared with VBL. 690 In patients with refractory ascites or infection, data from observational studies are contradictory regarding the safety of NSBBs for primary prophylaxis of variceal bleeding, and the choice and doses of NSBBs should be individualised.…”
Section: Variceal Bleedingmentioning
confidence: 99%
“…Based on low-certainty evidence, a Cochrane meta-analysis showed that beta-blockers, VBL, sclerotherapy and beta-blockers plus nitrates may decrease mortality compared with no intervention in cirrhotic patients with highrisk oesophageal varices without previous bleeding. 689 According to a systematic review with network metaanalysis, monotherapy with nonselective beta-blockers (NSBBs) may decrease all-cause mortality and the risk of first variceal bleeding in patients with cirrhosis with large oesophageal varices and carries a lower risk of serious complications compared with VBL. 690 In patients with refractory ascites or infection, data from observational studies are contradictory regarding the safety of NSBBs for primary prophylaxis of variceal bleeding, and the choice and doses of NSBBs should be individualised.…”
Section: Variceal Bleedingmentioning
confidence: 99%
“…An additional positive effect was observed by adding ligation of varices (only one trial), but there were more serious adverse events in the banding groups as compared to monotherapy with NSBB. The evidence for these findings are classified as uncertain, mainly because of low number of cases in the individual trials and the quality of the studies ( 120 ).…”
Section: Indications For Nsbbs Results From Randomized Trialsmentioning
confidence: 99%
“…In the first meta-analysis ( 119 ) of individual patient data (589 pts from 4 RCT) 2-year-survival was similar (68% placebo vs. 71% NSBBs). A significant beneficial effect on survival in the setting of primary bleeding prophylaxis as compared to no active intervention was described in a very recent network-meta-analysis on 6,653 patients, however with only marginal differences when NSBBs were compared to variceal ligation with and without additional NSBBs ( 120 ). A competing risk meta-analysis of 11 RCT trials comprising individual data of 1,400 patients in the setting of prevention of bleeding from high risk varices showed that NSBBs alone or in combination with ligation achieved a better survival than ligation alone in patients with compensated cirrhosis, but not in patients with decompensated cirrhosis ( 121 ).…”
Section: Indications For Nsbbs Results From Randomized Trialsmentioning
confidence: 99%
“…In light of the evidence available, we gave moderate strength to the neutral and optimistic priors. Regarding the neutral prior, this was for the following reasons: first, there was no clear signal from the meta-analysis of primary prevention studies for the reduction in non-bleeding decompensation with beta-blocker treatment, 20 and second there was clinical equipoise at the time the trial commenced regarding a beneficial effect of NSBB in compensated cirrhosis for the prevention of non-bleeding decompensation. In addition, in preparation for these analyses, we also undertook a post hoc analysis of a major primary prevention study in persons with large varices considering only those without decompensation at baseline 8 .…”
Section: Methodsmentioning
confidence: 99%